Tectaria moranii (Tectariaceae), a new fern species from Costa Rica - Tang, Guang-Da; Zhang, Li-Bing (Phytotaxa, 2018)
A new fern species, Tectaria moranii (sect. Tectaria; Tectariaceae), is described from central Costa Rica. Tectaria moranii is most similar to T. vivipara in having rachis bulbils, but the two are distinguishable by the habit of rhizome, shape of lamina, petiole and rachis color, proliferability of rachis bulbils, number of pairs of pinnae per lamina, pinna width, and sorus distribution. Tectaria moranii is assigned LC-Least Concern category following the IUCN guidelines.